A comparative study on defect estimation using XPS and Raman spectroscopy in few layer nanographitic structures. Issue 32 (22nd July 2016) - Ganesan, K.; Ghosh, Subrata; Gopala Krishna, Nanda; Ilango, S.; Kamruddin, M.; Tyagi, A. K.
Abstract : Defects in planar and vertically oriented nanographitic structures (NGSs) synthesized by plasma enhanced chemical vapor deposition (PECVD) have been investigated using Raman and X-ray photoelectron spectroscopy. Abstract : Defects in planar and vertically oriented nanographitic structures (NGSs) synthesized by plasma enhanced chemical vapor deposition (PECVD) have been investigated using Raman and X-ray photoelectron spectroscopy. While Raman spectra reveal the dominance of vacancy and boundary type defects respectively in vertical and planar NGSs, XPS provides additional information on vacancy related defect peaks in the C 1s spectrum, which originate from non-conjugated carbon atoms in the hexagonal lattice. Although an excellent correlation prevails between these two techniques, our results show that estimation of surface defects by XPS is more accurate than Raman analysis. Nuances of these techniques are discussed in the context of assessing defects in nanographitic structures.